The Oxford Handbook of Deliberative Democracy 2018
DOI: 10.1093/oxfordhb/9780198747369.013.50
|View full text |Cite
|
Sign up to set email alerts
|

Deliberative Democracy

Abstract: We define deliberation minimally to mean mutual communication that involves weighing and reflecting on preferences, values, and interests regarding matters of common concern. Deliberative democracy incorporates the requirements that deliberation take place in contexts of equal recognition, respect, reciprocity, and sufficiently equal power for communicative influence to function. These aspirational ideals have inspired a flourishing field, with theoretical and empirical research across many disciplines, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
127
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 0 publications
2
127
0
7
Order By: Relevance
“…Benhabib 1996), the ideal is blind to many systematic differences, such as structural injustices. Consequently, 'second generation' ideals of deliberative democracy, which are generally more realistic and attuned to actual political challenges, have been introduced within the tradition (Bächtiger 2018). For instance, Beauvais (2018), Beauvais and Bächtiger (2016) and Young (2011) have suggested that the abstract ideal of universal moral equality underlying the 'first generation' ideal of rational deliberation should be complemented with more situated ideals of equity and justice.…”
Section: A Defence Of Deliberative Democracy and Democratic Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…Benhabib 1996), the ideal is blind to many systematic differences, such as structural injustices. Consequently, 'second generation' ideals of deliberative democracy, which are generally more realistic and attuned to actual political challenges, have been introduced within the tradition (Bächtiger 2018). For instance, Beauvais (2018), Beauvais and Bächtiger (2016) and Young (2011) have suggested that the abstract ideal of universal moral equality underlying the 'first generation' ideal of rational deliberation should be complemented with more situated ideals of equity and justice.…”
Section: A Defence Of Deliberative Democracy and Democratic Educationmentioning
confidence: 99%
“…The latter are rooted in the recognition of the significant differences between different social groups in their access to wealth and power as well as their physical, cognitive and linguistic styles and abilities (Beauvais 2018). The later representatives of the deliberative tradition have thus adjusted the deliberative ideal by making it more sensitive to the pluralist aspirations and dimensions of modern democracies (Bächtiger et al 2018). For example, as Bächtiger et al (2018) point out, the sole focus on reasons and argumentation has evolved into the criterion that arguments ought to give and respond to appropriate 'considerations', including emotionally rooted expressions and differing styles of communication.…”
Section: A Defence Of Deliberative Democracy and Democratic Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, arguments, reason and facts should undergird public debate prior to decision-making and "[p]ost-truth politics is the antithesis of deliberative democracy." 23 This measure declines precipitously in countries where disinformation and populism is on the rise such as Brazil, Bulgaria, Czech Republic, India, Poland, and the United States of America.…”
Section: Deliberative Aspects: Toxic Polarization On the Risementioning
confidence: 99%